RELATIONSHIPS BETWEEN THE PLASMA ENVIRONMENT AND THE COMPOSITION AND OPTICAL-PROPERTIES OF PLASMA-POLYMERIZED THIN-FILMS PRODUCED IN RF DISCHARGES OF C2H2-SF6 MIXTURES - Durrant, S. F.; Mota, Rogério Pinto [UNESP]; Demoraes, MAB (American Institute of Physics (AIP), 1992)
Polymer films were grown in rf discharges containing different proportions of C2H2 and SF6. Quantitative optical emission spectrometry (actinometry) was used to follow the trends in the plasma concentrations of the species H and F, and more tentatively, of CH, CF, and CF2, as a function of the feed composition. Infrared spectroscopy revealed the density of CH and CF bonds in the deposited material. As the partial pressure of SF6 in the feed was increased, the degree of fluorination of the polymer also rose. The form of the dependency of the deposition rate on the proportion of SF6 in the feed was in good qualitative agreement with the activated growth model. From transmission ultraviolet visible spectroscopy data the refractive index and the absorption coefficient of the polymers were calculated as a function of the deposition parameters. Since the optical gap depended to some extent upon the degree of fluorination, it could, within limits, be determined by a suitable choice of the proportion of SF6 in the feed. A qualitative explanation of this relationship is given.